A Study of Product Portfolio of Refrigerated and Frozen Product Offerings by Gujarat Dairy Cooperatives - , Zeel Modi, Mahendra D. Gurjar (Archives of Current Research International, 2025)
The present study explores the strategic diversification of value-added dairy and non-dairy products developed by Gujarat-based cooperatives, with a focus on GCMMF’s flagship brand, Amul. The research investigates how these cooperatives have evolved their product portfolios beyond traditional liquid milk to include a wide array of refrigerated and frozen items such as ice creams, cheeses, paneer variants, and gourmet frozen foods. Employing a descriptive research design and secondary data analysis, the study examines product variety, packaging, shelf life, usage applications, nutritional considerations, and distribution reach across general trade, modern retail, and e-commerce platforms. Key findings highlight that Amul’s ice cream portfolio offers a balanced mix of traditional Indian flavors (Rajbhog, Kesar Pista) and Western variants (Cookies N Cream), in diverse formats—cones, cups, combo packs, and family tubs—tailored for different consumption occasions. The cheese portfolio showcases a wide range of processed, spreadable, gourmet, and flavored cheese products designed for both everyday use and gourmet experiences. The paneer product range offers refrigerated, frozen, and ambient variants, making it adaptable for diverse storage and culinary requirements, with notable presence in international markets. The gourmet frozen food segment—featuring pizzas, parathas, burger patties, fries, and snacks—demonstrates Amul’s responsiveness to urban consumer demand for convenience, nutrition, and fusion flavors.